EFEK MODEL PEMBELAJARAN INQUIRY TRAINING TERHADAP HASIL BELAJAR FISIKA SISWA SMA - ERNI KUSRINI SITINJAK (JURNAL ILMIAH MAKSITEK, 2019)
The purpose of this research was to analyze students learning outcomes taught by Inquiry Training model is better thanstudent learning outcomes taught with conventional learning.The population of this research were all studenst in class XSMA Swasta Bersama Berastagi. The sample of this research was taken by using cluster random sampling from around3 classes of SMA Bersama Berastagi consisting of 78 students. The X-1 as Experimental class using a model InquiryTraining as many as 30 peoples . X-3 as a control class using conventional teaching models 30 peoples. The result ofdata analysis using t test show that t test = 752, 8 dan t table = 1,673 so that ttest > ttable. It can be concluded that there isan influence on student learning outcomes using Inquiry Training Models.